NEW WAYS OF TEACHING WRITING EFFICIENTLY - Yuldosheva Dilbarkhon Saidakhmedovna (Galaxy International Interdisciplinary Research Journal, 2022)
Writing is one of the important means of teaching foreign language speech, an important initial stage in the development of productive communicative activity. But, unfortunately, in our general education school, teaching writing was given secondary importance for a very long time. Writing was only a means of teaching other types of speech activity, a means that allowed students to better master the language material.